KERJASAMA PEMERINTAH NANGGROE ACEH DARUSSALAM (NAD) DENGAN BANK DUNIA DALAM PROGRAM CONSOLIDATING PEACEFUL DEVELOPMENT IN ACEH 2009-2013 - Devi, Yenni Sari; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study will analyze about the Nanggroe Aceh Darussalam government cooperation with the World Bank in the program Consolidating Peaceful Development in Aceh 2009-2013. Assistance from the World Bank in the pack in CPDA program to the Government of NAD is an expression of solidarity and sympathy to the tsunami and the conflict that hit Aceh GAM ago.The process of cooperation between the Government of NAD with the World Bank in the program Consolidating Peaceful Development in Aceh realization is realized with improved aid development planning and management of public funds by the principle that break the cycle of violence in conflict areas in need of development and has a strong institutional legitimacy.PECAPP (Public Expenditure Analysis and Capacity Strengthening Program) is a program that works in the Public Finance sector and initiated by the World Bank with financial support from AusAID through the CPDA - World Bank.Keywords: CPDA,World Bank, Consolidating, PECAPP